Expression profiling and bioinformatics analysis of circulating microRNAs in patients with acute myocardial infarction. Issue 3 (12th November 2019) - Zhong, Zhixiong; Wu, Heming; Zhong, Wei; Zhang, Qifeng; Yu, Zhikang
Abstract: Objective: Acute Myocardial Infarction (AMI) is the most severe type of coronary atherosclerotic heart diseases. MiRNA is a class of endogenous noncoding small molecule RNA, which plays an important regulatory role in the development of some diseases. Methods: We examined the miRNA expression profiles in 16 patients with AMI compared with 6 non‐AMI controls using RNA sequencing. Results: Compared with the miRNA expression profiles of non‐AMI controls, a total of 181 differentially expressed miRNAs were discriminated in AMI patients, of which 96 upregulated miRNAs and 85 downregulated miRNAs. The top ten upregulated miRNAs were as follows: miR‐449a‐5p, miR‐126‐5p, miR‐93‐5p, miR‐199a‐3p, miR‐4454, miR‐6880‐3p, miR‐3135a, miR‐548ad‐5p, miR‐4508, and miR‐556‐5p; while the top ten downregulated were as follows: miR‐6805‐5p, miR‐1228‐5p, miR‐939‐5p, miR‐615‐3p, miR‐6780a‐5p, miR‐6857‐3p, miR‐5088‐55p, miR‐7155‐3p, miR‐184, and miR‐4525. And the qRT‐PCR results of differentially expressed miRNAs showed the same result as high‐throughput sequencing data. For these 181 differentially expressed miRNAs, 19 841 target genes were predicted by GO analysis. The enrichment analysis revealed 2061 involved in biological processes, 353 in molecular function and 303 in cellular components. To identify biological pathways in AMI as compared to non‐AMI, the target genes of differentially expressed miRNAs were mapped to the classical signal transduction pathway in KEGG, indicating that 214 classes were enriched. ROC analysis showed that the circulating miRNAs had the important value for AMI diagnosis and supported the previous conclusions that circulating miRNAs were effective to diagnose the AMI as a novel biomarker. Conclusions: Our findings require further research to confirm. It may provide a meaningful reference for the diagnosis and treatment of AMI.